TRADISI KOMUNIKASI SIMBOLIK DAN KONSTRUKSI MAKNA BUDAYA PETUGAS JENANG PADA MASYARAKAT LEMBAK KOTA BENGKULU - Indah Masruroh; Erwin Rochmansyah (Al-Idaroh: Media Pemikiran Manajemen Dakwah, 2026)
This research aims to describe how indigenous people in Bengkulu City welcome guests. The role of the language and culture of the waiter, known as Jenang, is symbolic in the process of serving various dishes. The food menu served in front of guests by jenang apparently has its own meaning. This tradition not only functions as a social activity, but also as a means of cultural da'wah that shows how Islamic teachings about honoring guests are implemented in real action. This research method uses a qualitative approach. Data sources were obtained from observation, interviews and documentation. The data analysis technique uses triangulation. The results of this research show that there are special requirements for someone to serve as a Jenang officer, and not just anyone can carry out the duties and roles. Then, there are many meanings to the simple menu served. The number of dishes must be odd, not including rice. Of course, this is a unique feature of tradition which indicates that local traditions can be a stronghold of Islamic values ​​as well as a media for preaching that is contextual and relevant throughout time.